The Double Stigma of Limited Literacy and Mental Illness: Examining Barriers to Recovery and Participation among Public Mental Health Service Users. (November 2017) - Lincoln, Alisa K.; Adams, Wallis; Eyllon, Mara; Garverich, Suzanne; Prener, Christopher G.; Griffith, John; Paasche-Orlow, Michael K.; Hopper, Kim
The disadvantaged social position of public mental health service users reflects synergistic relationships among tangible disadvantage and stigma and its consequences. Limited literacy, an important factor in social disadvantage and an additional source of stigma, is virtually absent from the discussion. Employing a mixed-methods, service user–informed design, we explore the meaning and impact of limited literacy in the lives of public mental health service users in the United States. Of 267 participants, 184 (69 percent) read at or below an eighth-grade level. Next, we demonstrate levels of and explore relationships among both literacy and mental illness concealment stigma and stigma consciousness (for mental illness). Finally, informed by our qualitative data, we describe how people encounter and manage this double burden of stigma with respect to: contexts of concealment, dilemmas of disclosure, and reduction and exclusion. Limited literacy and its associated stigma are important and underexamined barriers to mental health, well-being, recovery, and social inclusion for public mental health service users. Future work should include further examination of the multiple and layered stigmas in the lives of people with serious mental illness.